Assessing Trustworthiness in Research: A Pilot Study on CV Verification - Phillips, Trisha (J Empir Res Hum Res Ethics, 2019)
When scholars express concern about trust in science, they often focus on whether the public trusts research findings. This study explores a different dimension of trust and examines whether and how frequently researchers misrepresent their research accomplishments when applying for a faculty position. We collected all of the vitae submitted for faculty positions at a large research university for 1 year and reviewed a 10% sample for accuracy. Of the 180 applicants whose vitae we analyzed, 141 (78%) claimed to have at least one publication, and 79 of these 141 (56%) listed at least one publication that was unverifiable or inaccurate in a self-promoting way. We discuss the nature and implications of our findings, and suggest best practices for both applicants and search committees in presenting and reviewing vitae.